Pengenalan Konsep Koding Dan Algoritma Sederhana Untuk Siswa SD Melalui Media Interaktif Berbasis Deep Learning : Pengabdian - Dewi Juniayanti; Dewa Ayu Made Manu Okta Priantini; I Gusti Ngurah Santika; Wehelsinta Olsiana Ngongo; Maria Oswin Yolansiana; Yasinta Baruk (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program aims to introduce basic coding and simple algorithm concepts to fifth-grade students at SD Insan Prestasi through an unplugged learning approach that does not require computers. This approach was chosen to develop early computational thinking skills, particularly sequencing, pattern recognition, and logical problem-solving. The activity consisted of three stages: preparation, implementation, and reflection. During the preparation stage, the team provided instructional cards (move forward, backward, turn), game boards, arithmetic coding tasks, pattern-coding cards, picture coding sheets, and puzzle fragments as rewards. In the implementation stage, students completed three main games arithmetic coding, pattern coding, and picture coding combined with numbers. Each successfully completed game rewarded students with puzzle fragments, and the group that managed to assemble the complete puzzle became the winner. In the reflection stage, students discussed their strategies, identified errors, and connected their experiences to programming concepts such as sequencing, looping, and branching. The results indicate that students demonstrated improved logical reasoning, better understanding of instruction-result relationships, and increased engagement. The unplugged approach proved effective as an introductory method for aching coding and algorithmic thinking to elementary school students.